ChemInform Abstract: Stereoselective Synthesis of Medium‐Sized Cyclic Ethers: Application of C‐Glycosylation Chemistry to Seven‐ to Nine‐Membered Lactone‐Derived Thioacetals and Their Sulfone Counterparts. Issue 31 (5th August 2014) - Suga, Yuto; Fuwa, Haruhiko; Sasaki, Makoto
Abstract A number of α‐substituted medium sized cyclic ethers are prepared in an efficient and stereoselective manner.